Effect of round curvature of anterior implant-supported zirconia frameworks: finite element analysis and in vitro study using digital image correlation. Issue 11 (18th August 2017) - Messias, Ana; Neto, Maria Augusta; Amaro, Ana Martins; Nicolau, Pedro; Roseiro, Luis Manuel
Abstract: Two groups of 4-unit zirconia frameworks were produced by CAD/CAM to simulate the restoration of an anterior edentulous gap supported by 2 implant-abutment assemblies. Group 1 comprised straight configuration frameworks and group 2 consisted of arched frameworks. Specimens were made with the same connector cross-section area and were cemented and submitted to static loads. Displacements were captured with two high-speed photographic cameras and analysed with video correlation system. Frameworks and the implant-abutment assembly were scanned and converted to 3DCAD objects by reverse engineering process. A specimen of each group was veneered and the corresponding 3D geometry was similarly obtained after scanning. Numerical models were created from the CAD objects and the FE analysis was performed on the zirconia frameworks and on the FPDs bi-layered with porcelain (veneered frameworks). Displacements were higher for the curved frameworks group, under any load. The predicted displacements correlated well with the experimental values of the two framework groups, but on the straight framework the experimental vertical displacements were superior to those predicted by the FEA. The results showed that the round curvature of zirconia anterior implant-supported FPDs plays a significant role on the deformation/stress of FPDs that cannot be neglected neither in testing nor in simulation and should be considered in the clinical setting.